AZ31 Magnesium Alloy Foils as Thin Anodes for Rechargeable Magnesium Batteries. Issue 21 (31st August 2021) - Maddegalla, Ananya; Mukherjee, Ayan; Blázquez, J. Alberto; Azaceta, Eneko; Leonet, Olatz; Mainar, Aroa R.; Kovalevsky, Aleksey; Sharon, Daniel; Martin, Jean‐Frédéric; Sotta, Dane; Ein‐Eli, Yair; Aurbach, Doron; et al.
Abstract: In recent decades, rechargeable Mg batteries (RMBs) technologies have attracted much attention because the use of thin Mg foil anodes may enable development of high‐energy‐density batteries. One of the most critical challenges for RMBs is finding suitable electrolyte solutions that enable efficient and reversible Mg cells operation. Most RMB studies concentrate on the development of novel electrolyte systems, while only few studies have focused on the practical feasibility of using pure metallic Mg as the anode material. Pure Mg metal anodes have been demonstrated to be useful in studying the fundamentals of nonaqueous Mg electrochemistry. However, pure Mg metal may not be suitable for mass production of ultrathin foils (<100 microns) due to its limited ductility. The metals industry overcomes this problem by using ductile Mg alloys. Herein, the feasibility of processing ultrathin Mg anodes in electrochemical cells was demonstrated by using AZ31 Mg alloys (3 % Al; 1 % Zn). Thin‐film Mg AZ31 anodes presented reversible Mg dissolution and deposition behavior in complex ethereal Mg electrolytes solutions that was comparable to that of pure Mg foils. Moreover, it was demonstrated that secondary Mg battery prototypes comprising ultrathin AZ31 Mg alloy anodes (≈25 μm thick) and Mg x Mo6 S8 Chevrel‐phase cathodes exhibited cycling performance equal to that of similar cells containing thicker pure Mg foil anodes. The possibility of using ultrathin processable Mg metal anodes is an important step in the realization of rechargeable Mg batteries. Abstract : Ultra‐thin Mg alloy : Rechargeable magnesium batteries are considered as the most promising alternative to lithium battery technologies Similar electrochemical performance of 100 μm thick pure Mg foils and 25 μm thin and ductile AZ31 Mg alloy foils as anodes in rechargeable Mg batteries is demonstrated. Comprising Chevrel‐phase (Mo6 S8 ) cathodes, thin foils of AZ31 Mg alloy can serve as very suitable anodes in rechargeable Mg batteries.